Intestinal obstruction caused by small bowel entrapment within a lumbar fracture: A case report. Issue 42 (21st October 2022) - Lee, Jin Suk; Kim, Se Heon; Lee, Jin Young; Ye, Jin Bong; Sul, Young Hoon; Seok, Junepill; Yoon, Su Young; Kim, Hong Rye; Choi, Jung Hee; Kim, Yook
Abstract : Introduction: Intestinal obstruction associated with traumatic vertebral fracture is extremely rare. We report a case of obstructive small bowel injury caused by entrapment of the small intestine at the fracture site of the 5 th lumbar vertebra due to trauma. Case presentation: A 55-year-old man fell from a height of 4 m and visited the emergency room of a local hospital with complain of back pain. During the examination, a 5 th lumbar vertebral body fracture and left psoas muscle hematoma were observed, and the patient was admitted to the neurosurgery department for conservative treatment. The patient received conservative treatment for 2 days, but new symptoms of intestinal obstruction and fever occurred. A neurosurgeon at the hospital suspected duodenal perforation and transferred the patient to the regional trauma center for treatment. Our medical staff reviewed the patient's symptoms and imaging data and decided to perform an emergency operation because of small bowel entrapment in the 5 th lumbar vertebrae fracture and perforation of the small intestine. We found that the small bowel, approximately 160 cm below the ligament of Treitz, was incarcerated at the 5 th lumbar vertebral fracture site. After careful manual reduction of the entrapment of the small intestine, a small bowel resection of 25 cm, including the injury site, was performed with anastomosis. Conclusion: If symptoms of intestinal obstruction are observed in patients with traumatic spinal injury, medical staff must consider the exceedingly rare possibility of bowel entrapment.